Aktivitas Wanita di Sektor Publik dalam Pemberitaan Surat Kabar - Sari Anggreni, Likha (Jurnal Ilmu Komunikasi, 2014)
Abstract: The representation of women and men in public discourse are often problematic. In everyday discourse, women are still considered as secondary and inferior to men. This presents a problem when taking discourses on women into media realm. The profile of workingwomen is often displayed in media mainly through male viewpoint. This study aims to look at the media coverage of women success in public sector. The framing analysis method is used to analyse the framing issues of workingwomen in Suara Merdeka newspaper. The study found that the representation of workingwomen in Suara Merdeka is still dominated by male perspective.Â Abstrak: Gambaran perempuan dan laki-laki dalam wacana publik sering kali masih problematik. Dalam wacana sehari-hari, perempuan masih dinomorduakan. Problem ini menjadi lebih kompleks saat masuk ke ranah media. Profil perempuan pekerja sering ditampilkan melalui perspektif laki-laki. Studi ini bertujuan untuk melihat pemberitaan media mengenai keberhasilan perempuan di sektor publik. Metode analisis framing dipakai untuk memdedah pembingkaian isu-isu wanita pekerja dalam surat kabar Suara Merdeka. Hasil analisis menunjukkan bahwa representasi perempuan pekerja di surat kabar Suara Merdeka masih didominasi oleh sudut pandang laki-laki.